MEMBANGUN TOLERANSI BERAGAMA BERLANDASKAN KONSEP MODERASI DALAM AL-QUR’AN DAN PANCASILA - Hilmi Ridho (An Natiq, 2021)
The issue of intolerance in the name of Islam has increasingly made people traumatized and restless by the decline in human values. Every day, the world is offered a display of Islam that is delivered by angry Muslims. The world also wonders where is the rahmah's behavior from religion which is said to carry the teachings of mercy and compassion. When there are groups that raise the flag of Islam while destroying humanity, the world is increasingly questioning the practice of Islam that rahmatan lil 'alamin, peace, and respect for humans. The decline in the value of humanity and tolerance is influenced by a weak understanding of the teachings of moderate Islam and the inclusion of Wahhabism as the ancestors of radicalism. This paper is examined as a form of concern for what has befallen Islam with the treatment that has no humanity. The Koran as a source of Islamic religious law with its verses, provides us with an understanding of the meaning of moderate Islam that is true. Whereas Pancasila as an absolute source of law in Indonesia gives the meaning of religious tolerance through all the principles of Pancasila; God, humanity, unity and justice. These two sources of law should be applied in daily life as a solution to overcome intolerance that often carries the name of Islam as a tool to fight other religions that are not in line with the teachings of Islam.Â